INFRA-TRADE NET WORKS, SOCIAL PROMOTION STRATEGIES AND LEGAL STATEMENTS. MAGELLAN , 1899. - Boric Bargetto, Ljuba (Revista de Historia Social y de las Mentalidades, 2016)
From the micro-historical study of a court case corresponding to a theft executed by inmigrant Croatian Juan Spanich in Punta Arenas in 1899, it is intended to mean and valuate those aspects that can contribute to the reconstruction and questioning of an immigration society, and thus present the gap existing in relation to judicial topics in the current historiography regarding migration studies. In this sense, this article will show the development of networks of infra- trade and solidarity networks as recurring practices by immigrants in a society of emerging business growth, marked by credit systems, bonds and social promotion mechanisms, i.e. cultural elements as the " honor", "respect" and "public fame," which transcended spheres of social and articulated as symbolic discourses in judicial contexts.